The Role of Dietary Fiber in Reducing the Risk of Depression Among Young Adults: A Literature Review - Ulfi Rahma Yunita; Idri Iqra Fikha; Fathia Maulida (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Depression among young adults is on the rise globally, with a prevalence of approximately 2% among those aged 15–24 in Indonesia. One contributing factor is the shift toward modern diets low in dietary fiber, which impacts mental health. Dietary fiber is known to play a crucial role in maintaining gut microbiota balance, reducing systemic inflammation, and influencing the gut-brain axis. This literature review aims to synthesize the latest scientific evidence regarding the role of dietary fiber in reducing the risk of depression among young adults. The study was conducted using a systematic narrative review method through a search of articles in the PubMed, Web of Knowledge, and Google Scholar databases, published between 2020 and 2025. Of the seven studies reviewed, six met the inclusion criteria with a cross-sectional design, and one was a prospective longitudinal study. The study populations included Korea, the United States, Iran, Australia, and China. Although various depression assessment instruments were used (SDS, PHQ-9, HADS, BDI-Y, GHQ), all studies showed consistent results indicating that higher dietary fiber intake is associated with a reduced risk of depression, anxiety, and psychological distress. This protective effect is believed to be mediated by anti-inflammatory activity and increased production of short-chain fatty acids (SCFAs).